Dari Kesaksian Iman ke Simbiosis Agama: Meninjau Konsep Dialog Calvin E. Shenk Bagi Perjumpaan Islam-Kristen di Maluku - Yohanes Parihala; Kritsno Saptenno (UIN Sunan Gunung Djati Bandung, 2020)
This study aims to analyse the thoughts of Calvin E. Shenk, a Christian missiologist, who criticized the concept of tripolar typology in the reality of religious pluralism, which was seen as reducing Christian faith. Calvin E. Shenk offers the idea of authentic dialogue, dialogue is as a form of witness of faith. However, Shenk's thoughts cannot simply be applied in the reality of encounters between Muslims and Christians in Maluku, which only emerged from the religious conflict of in 1999-2004. Both the analysis of Shenk's thoughts and the analysis of the context of religious presentation in Maluku, uses the approach of literature study in qualitative research methods. Finally, this study offers a dialogue paradigm in the context of interfaith relations in Maluku that embraces the uniqueness of each religion, including the praxis of the witness of faith, but does not neglect an important dimension that all religions need each other, and that is the symbiosis of religion.